DAMPAK PERUBAHAN IKLIM TERHADAP USAHATANI PADI DI DESA WANGUK KECAMATAN ANJATAN KABUPATEN INDRAMAYU - Getmi Nuraisah; Rani Andriani Budi Kusumo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
One of the biggest threats in the world of agriculture is the occurrence of global climate change which is likely to result in crop failure. Agriculture and climate change have a very close connection, because agricultural sector is very dependent and very vulnerable to climate change, so that the knowledge of farmers in the magnitude of climate change is needed. This study aims to examine the extent to which farmers' knowledge of climate change is happening and the impacts caused by climate change, especially on rice. This research was carried out using qualitative design with "case study" techniques, using primary data and secondary data. Determination of informants was carried out purposively, namely farmers who had done farming for ± 10 years who experienced crop failure and who were not with their land ownership status. Data collection techniques used in the form of observation, interviews and literature studies. The design of data analysis uses descriptive analysis. The results of this study indicate that farmers who experience crop failure and who have harvested already know and feel the changes that occur such as changes in planting, changes in temperature, changes in rainfall, extreme weather, and pest attacks, but farmers have not been able to explain what climate change own. The impact felt by farmers due to climate change is that farmers experience a decline in yields, increased pest attacks, increased risk of crop failure and a decrease in farmers' income.